Govardhan pillars - Temples of India Project Team (Jio Institute, 2024)
These pillars, popularly called Govardhan pillars, are quite common in several regions of Rajasthan, particularly the more arid regions of Thar and Maru. Although they may not always feature the image of Govardhan-Krishna in all cases. The top of the pillar is shaped like a temple and the niches on three sides have images of Ganesha, Vishnu and Shiva, while what appears to be the principal face has two niches. The lower one has two male figures standing erect with closed hands and the upper one has two such figures worshipping the Shivalinga. Govardhan pillars are commonly, though not always, erected to commemorate the deceased, and this also seems to be the case with our pillar as well.